Saturday

March 28, 2015

March 28, 2015

Posted by **Sara** on Tuesday, September 23, 2008 at 4:22pm.

-2(z + 11)=6

thank you

- 8th grade -
**bobpursley**, Tuesday, September 23, 2008 at 4:24pmmultiply the parenthesis by -2

-2z-22=6

add 22 to each side.

-2z=28

divide both sides by -2

z=-14

- 8th grade -
**Ms. Sue**, Tuesday, September 23, 2008 at 4:26pm-2(z + 11)=6

First, multiply:

-2z - 22 = 6

Then, to combine like terms, add 22 to both sides of the equation.

-2z - 22 + 22 = 6 + 22

-2z = 28

z = -14

You can prove this answer by substituting -14 for z in your original problem.

**Answer this Question**

**Related Questions**

math-radical equations - Here's one of the questions I have problems with: cube ...

math-radical equations - Here's one of the questions I have problems with: cube ...

8th Grade Math - How do you solve this equations? (xy^-3)^-5 (3x^4)(4x^12) ab^-6...

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

8th grade Algebra I (junior level math) - Hello, I am currently in Unit 4-1 (...

Substitution Method in Algebra - I'm having trouble with the last one too. Could...

Algebra - Can someone please help me with math problem and explain to me step by...

8th Grade Algebra - I missed the lesson for this unit. (=sqaure root sign How do...

8th grade Algebra I (junior level math) - How do i solve proportions? step by ...

Algebra II- please help! - I just cannot seem to be able to grasp the concept of...